2019
DOI: 10.1371/journal.pone.0218510
|View full text |Cite
|
Sign up to set email alerts
|

Urate-lowering agents for asymptomatic hyperuricemia in stage 3 – 4 chronic kidney disease: Controversial role of kidney function

Abstract: Because the serum uric acid level increases as the glomerular filtration rate (GFR) decreases, hyperuricemia is associated with chronic kidney disease (CKD). Although hyperuricemia is a risk factor for CKD progression, the causal role of uric acid remains controversial in patients with CKD and asymptomatic hyperuricemia. This study included 588 patients with stage 3-4 CKD and asymptomatic hyperuricemia. Using propensity score matching, 165 pairs treated and untreated with pharmacologic urate-lowering therapy w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…HUA is considered to be a major risk factor of metabolic disorders after hypertension, hyperlipidemia, and hyperglycemia [ 8 ], and is considered to be the major pathological basis of gout, whereby approximately 5–12% of HUA patients have the possibility of developing gout [ 9 ]. Moreover, a large number of epidemiological studies have reported that HUA is closely related to diabetes, hypertension, obesity, cardiovascular disease, and kidney disease [ 10 , 11 , 12 , 13 ], which suggests that complications associated with HUA may increase in the coming years.…”
Section: Introductionmentioning
confidence: 99%
“…HUA is considered to be a major risk factor of metabolic disorders after hypertension, hyperlipidemia, and hyperglycemia [ 8 ], and is considered to be the major pathological basis of gout, whereby approximately 5–12% of HUA patients have the possibility of developing gout [ 9 ]. Moreover, a large number of epidemiological studies have reported that HUA is closely related to diabetes, hypertension, obesity, cardiovascular disease, and kidney disease [ 10 , 11 , 12 , 13 ], which suggests that complications associated with HUA may increase in the coming years.…”
Section: Introductionmentioning
confidence: 99%
“…Uric acid is a product of purine metabolism and is mainly excreted by kidneys (19). Consequently, hyperuricemia is highly prevalent in CKD patients (20). So, UA serum concentration depends on the rate of purine metabolism and the efficiency of its renal clearance, which is easily affected by dialysis (21).…”
Section: Discussionmentioning
confidence: 99%
“…UA increases renal inflammation and fibrosis [ 14 ], and UA crystals cause gouty nephropathy in basic studies [ 15 , 16 ]. Some observational studies have demonstrated the detrimental effect of hyperuricemia in CKD patients [ 17 ], but some studies disagree [ 18 ]. One explanation is that the progression of CKD elevates UA via reduced renal excretion [ 19 ].…”
Section: Introductionmentioning
confidence: 99%